Is there a common pattern of dental specialties in the world? Orthodontics, the constant element - Ignacio Garcia-Espona; Cristina Garcia-Espona; José Antonio Alarcón; Eugenia Garcia-Espona; Javier Fernández-Serrano (BMC, 2024)
Abstract Background There is a lack of studies comparing the status of dental specialties worldwide. Therefore, this study aimed to analyze the differences and similarities between the number and types of dental specialties in 31 countries, including every continent, in the world. Materials and methods Available official documents and webpages from regulatory bodies, official colleges and councils, and dental institutions were collected from 31 countries and analyzed to obtain reliable data on dental specialties. Differences were analyzed using the Lorentz curve and Gini test. Additionally, a cluster analysis was performed to obtain groups of countries with similar patterns in the number and types of dental specialties. Results A total of 32 different specialties were officially recognized among all the analyzed countries. Orthodontics and oral surgery (100% and 93.1%, respectively) were the two most frequently officially recognized dental specialties worldwide. The total global degree of inequality in the 31 analyzed countries was 42.4%. The Anglo-Saxon countries showed the greatest similarity, approximately 15-fold higher than the European countries. Cluster analysis differentiated six main groups of countries according to the number and types of dental specialties. European countries formed one of the two largest clusters, and the other cluster was of Anglo-Saxon, Asian, African, and several Eastern European countries with a high number of specialties. Conclusions Officially recognized dental specialties in the different continents and countries show an asymmetric organization. The number, names, and skills of officially recognized dental specialties exhibited significant differences, showing inequalities in their organization. The Anglo-Saxon pattern of dental specialties showed greater equality than the European pattern. Orthodontics was the only constant element among the different patterns.